Impact of creative capacity building of local innovators and communities on income, welfare and attitudes in Uganda - Nkonya, Ephraim M.; Bashaasha, Bernard; Kato, Edward; Bagamba, Fredrick; Danet, Marion (International Initiative for Impact Evaluation, 2020)
Technologies and innovations are key drivers of human development and competitiveness. The failure of imported technologies has galvanised efforts to develop technologies generated through close collaboration between external investors and local communities. The general objective of the study was to determine the impact of creative capacity building (CCB) training on human welfare and local communities’ perceptions of their ability to innovate. Specifically, the study targeted a number of major outcomes of CCB training, namely: economic impacts; behavioural changes; attitudinal change; and technology creation and use, including policy influence. CCB is a hands-on training approach whose students are community members of any educational level. CCB focuses on harnessing local creativity and indigenous knowledge in the technology design process, facilitating community innovations and invention. In skills training workshops, trainees work collaboratively to design and develop tools that meet their needs. The training encourages and trains people to make technologies that generate income, improve health and safety, save labour and time, and change perceptions about themselves.